Environmental sustainability practices of immigrant-owned small and medium enterprises in South Africa - Fakoti, O. (European Review of Applied Sociology, 2018)
Environmental sustainability of immigrant-owned small and medium enterprises (SMEs) is important to a country’s long-term sustainable development. The study investigated the environmental sustainability practices (ESP) of immigrant-owned SMEs. In addition, the study examined the effect of demographic factors (age, gender and level of education) on ESP. The study also investigated the relationship between ESP and financial performance of SMEs. Data was collected from one hundred and eighty two immigrant small business owners. The survey method (self-administered questionnaire) was used for data collection. The participants in the study were conveniently sampled. Descriptive statistics, T-test, Pearson correlation and regression analysis were used for data analysis. The results indicated that immigrant-owned SMEs are engaged in recycling, energy efficiency and reduction of waste and pollution. Their involvement in environmentally friendly products and environmental management policy is limited. Females exhibit higher levels of recycling, waste reduction energy efficiency and reduction of pollution. Age and level of education positively affect environmental sustainability practices. Waste reduction, energy efficiency and reduction of pollution have significant positive relationships with financial performance. Recommendations to improve EPS are suggested.
Article published in the European Review of Applied Sociology 28 Volume 11, Number 17, Year 2018
Keywords: Environmental sustainability practices; Demographic factors; Performance; Immigrants; Small and medium enterprises; South Africa; Small business -- South Africa; Immigrants -- South Africa